2022
DOI: 10.3390/ijerph19148769
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Late-Life Depression and Cognitive Function in Older Korean Adults: A Moderation Analysis of Physical Activity Combined with Lower-Body Muscle Strength

Abstract: Background: This study examined the relationship of physical activity (PA) combined with lower-body muscle strength to late-life depression and cognitive impairment in 10,097 participants (6062 females) ≥ 65 years of age. Methods: Exposures were PA, sit-to-stand test (STST), and depressive symptoms. Outcome was cognitive performance. Results: Depressed individuals had an increased risk of mild cognitive impairment (MCI; odds ratio (OR), adjusted OR = 1.845 and 95% confidence interval (CI) = 1.580–2.154, p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It has been observed that depressed patients often experience a decline in physical function, reflected in a decrease in SPPB scores. 22,23 A cross-sectional study revealed an association between SPPB levels and depression. 24 However, this previous study had limitations due to its crosssectional design, and further longitudinal investigations were necessary to establish a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that depressed patients often experience a decline in physical function, reflected in a decrease in SPPB scores. 22,23 A cross-sectional study revealed an association between SPPB levels and depression. 24 However, this previous study had limitations due to its crosssectional design, and further longitudinal investigations were necessary to establish a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The SPPB test includes measures of lower limb muscle strength, speed, and balance, which provide a comprehensive assessment of the lower limb physical performance in older adults. It has been observed that depressed patients often experience a decline in physical function, reflected in a decrease in SPPB scores 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Although depressive symptoms are frequently regarded as being prodromal indicators of clinical dementia, mounting evidence suggests that depressive symptoms in later stages of life may act as an independent risk factor for cognitive impairment [29]. Previous Korean studies have consistently demonstrated that depressive symptoms are associated with the development of cognitive impairment during advanced age [5,30,31]. Vascular diseases and elevated glucocorticoid levels have been postulated as representing a causal link between depression and cognitive impair-ment [10].…”
Section: Discussionmentioning
confidence: 99%